On the persistence of mouse urine odour to human observers: a review. (25th February 2016) - Kwak, Jae; Jackson, Marcus; Faranda, Adam; Osada, Kazumi; Tashiro, Takuya; Mori, Kenji; Quan, Ying; Voznessenskaya, Vera V.; Preti, George
Abstract: To the human nose, mice produce unique, persistent and potent odour which is widely assumed to be derived mainly from their urine. In this review, we discuss why the mouse odour is so potent and long‐lasting to the human nose. Sensory and chemical analyses have revealed that 2‐ sec ‐butyl‐4, 5‐dihydrothiazole (SBT) was the major mousy odorant and present almost exclusively in male urine. It is not depleted from urine even after repeated headspace or solvent extractions since its majority is tightly bound to the major urinary proteins (MUPs) in male mouse urine that serve to control the release. The urinary concentration of SBT is estimated to be around several hundred parts per million when the binding of SBT to MUPs is considered, while its human olfactory threshold is estimated to be approximately at the parts per billion level. Therefore, the strikingly persistent quality of mouse urine odour, mainly contributed by SBT, is explained by its low human olfactory threshold, its presence in urine at a high concentration, and its delayed release by MUPs. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The persistent quality of mouse urine odour, mainly contributed by 2‐ sec ‐butyl‐4, 5‐dihydrothiazole, is explained by its low human olfactory threshold, its presence in urine at a high concentration, and its slow release by the major urinary proteins.